Oily Ascites Revealing a Spontaneous Rupture of a Mature Ovarian Cystic Teratoma. Issue 1 (11th September 2020) - Colin, Paul-Emile; Deprez, Louis; Cousin, François
Teaching point: Ovarian teratoma rupture can manifest clinically as an acute or chronic syndrome, associated with specific imaging features, both characterized by intra-abdominal fatty fluid.